“O curso não forma a gente para ser professor”: representações sobre a licenciatura nos discursos institucionais dos cursos de Letras Espanhol de Minas Gerais: uma análise textualmente orientada dos Projetos Pedagógicos de Curso - Mariana Ferreira Ruas (2021)
The main objective of this doctoral research was to analyze the discursive constructed representations about the Spanish teacher education programs held at public educational institutions in Minas Gerais. We aimed to identify which meanings about the purposes of the programs are institutionally produced, as well as the profile desired for the alumni, observing which discourses cross the curricular documents, and the ones that are (re)produced in relation to teaching and the conceptions about the education of Spanish teachers. This investigation is situated in the fields of critical and post-critical curriculum theories (APPLE, 1989, 2006, 2016; GOODSON, 1991, 1997; LOPES, 2013; LOPES; MACEDO, 2011; SELLES, 2015; SILVA, 2014), we consider it as a discursive practice, and as a result of a broad social process, a space of power that involves not only the knowledge being taught, but the entire environment and subjects involved in the educational scope, thus they cannot be reduced to a physical and static educational object. Therefore, we analyzed a curricular document, the Course Pedagogical Projects (CPPs), of nine public institutions of the State of Minas Gerais that offer a major degree in teaching Spanish. We considered that this document establishes the operational basis of the programs and it explicates the institutional perspective that guides the decisions and curricular configurations. The corpus consisted of the CPPs sections dedicated to their general and specific objectives; the profile desired for the alumni; the reasons for the design of the teaching program, in addition to the National Curriculum Guidelines of the Spanish teaching undergraduate courses (MEC/CNE, 2002a, 2002b, 2015), documents that define and institute the operation and organization of higher education curricula. On the one hand, the analysis undertaken focused on the particular ways of representing the teaching programs and the students education, and on the other hand, on how the CPPs identify undergraduates, operationalizing the concepts of representational and actional meanings of Critical Discourse Analysis (CHOULIARAKI; FAIRCLOUGH, 1999; FAIRCLOUGH, 1992, 2003; RESENDE; RAMALHO, 2006). The theoretical choices for this investigation based on authors dedicated to the studies on curriculum and Spanish teacher education programs in Brazil (DAHER, 2011; FREITAS, 2012, 2018; SILVA JUNIOR; SANTOS, 2016; RODRIGUES, 2010). The results found from the documents analysis indicate that there are contradictory representations of the Teacher Program because, although it indicates its teacher education purposes, there are other profiles desired, building up a professional identification capable of acting in different areas besides teaching. On the other hand, we observed that the federal documents act as a homogenization factor in the PPCs discourses, and it is not possible to identify influences of local demand in representations about the education of Spanish teachers.